Debunking the Falsehoods of Historical Interpretations: Arnold Spekke on George Kennan’s “Soviet-American Relations, 1917–1920. The Decision to Intervene” - Selga, Marika (Journal of the University of Latvia. History | Latvijas Universitātes Žurnāls. Vēsture, 2023)
In the spring of 1958, Arnold Spekke, Charge d’Affaires in Washington D.C., having read George Kennan’s book “Soviet-American Relations, 1917–1920. The Decision to Intervene” decided to write a comment on certain facts expressed in the book. He concentrated on the description of the execution of Czar Nicholas II and his family, as well as the fact that the book did not mention the Latvian units that fought under Allied leadership, namely, the Troitsk battalion as part of the 3rd Czechoslovak Division. Spekke also submitted a letter written in 1928 by Nikolai Sokolov’s assistant, Captain Pavel Bulygin, in which it was confirmed that there were no Latvians among the shooters. Kennan in his response assured that his goal had only been to emphasize the cruelty with which the murder was committed. The preparation of comments contributed to the efforts of Latvians in exile to focus on writing down memories and studying Latvian history.